Retroclival hemorrhage due to blunt force head trauma: An autopsy case report - Priscilla Githinji (Forensic Science International: Reports, 2020)
Retroclival hemorrhages in adults are very rare and are mostly associated with trauma. Prompt diagnosis is usually very important to avoid neurological deficits and even death. We present a case of retroclival hemorrhage identified at autopsy in a 37 year old man who had a history of trauma.